Pedagogical studies in Latin America: Brazil from the teaching perspective - da Silva, Renan Antônio (Revista Chilena de Pedagogía, 2025)
The objective of this research is to analyze the Pedagogical Residence Program instituted by the Brazilian Federal Government as a social policy, in order to point out contributions and setbacks in relation to its implementation in Brazilian federal universities. By means of a bibliographic survey, it is qualitative-approach reasearch and it uses the critical theoretical references based on the discussions of Nóvoa, Contreras, Marcelo Garcia, Mellouki, and Gauthier to support the analysis related to the understanding of teacher education and public policy social programs. We use notes from Antonio Nóvoa (2009) to think about the creation of a teacher-training program considering the contemporary challenges. Studies show the need to redefine the pedagogical residence program so that we can advance in favor of a larger project for teacher education in Brazil.